Increase of Wheat (Triticum aestivum L.) Resistance to Leaf Rust (Puccinia tritici) via Gene Transformation - Tikász, Gabriella (Acta Agraria Debreceniensis, 2010)
Leaf rust is one of the most significant fungal disease of wheat not only in Hungary but also in other parts of the world. For improving leaf rust resistance of winter wheat variety (Hajdúság, 2003) produced by conventional breeding methods, verified by results of variety tests, showing outstanding results in the aspect of the most important economic values, integration of tissue culture technics, genetic engineering and traditionalmethods may provide facilities. Building the gene(s) responsible for resistance into the determined genome can improve the resistance in a way that changes other features of the plant slightly or not at all. In the course of genetical transformation of the variety Hajdúság we applied one of the wheat’s own effecient green-tissue specific insurer genetical regulator, the promoter of ribulose carboxylase 1-5 bisphosphate (RuBisCo) ‘s smallsubunit to control the expression of the gene cmg1.